Investigating the influence of wettability and direction on supercritical CO2 trapping for supercritical CO2-brine imbibition process at pore scale for bentheimer sandstone - Jahan, F.; Ahmed, S.; Hossain, Mofazzal (2018)
Copyright 2018, Society of Petroleum Engineers Wetting properties of various reservoir rocks strongly influence the efficiency and security of geological storage of carbon dioxide in deep saline aquifers. Numerical simulation of Carbon Capture and Storage (CCS) has become a considerable research option now-a-days due to less time and cost-effective outcomes compare to traditional laboratory based experiments. This study provides a Computational Fluid Dynamics (CFD) methodology for the pore-scale displacement mechanism of supercritical CO2 under different wetting conditions and quantify the effect of wettability and direction of flow on supercritical CO2 trapping. A 3-Dimensional visualization software is used to build surface mesh from the micro-pores of the Bentheimer sandstone. A module of a commercial CFD software is used to generate volume mesh from the surface mesh and another module from the same CFD software is used to perform imbibition processes (supercritical CO2/brine) through the Bentheimer sandstone. Full Navier-Stokes equations are solved by using Eulerian-Eulerian multiphase transient flow approach. Free surface flow model is used to integrate the effect of capillary forces. This model determines the pressure gradient at the two-phase interface. The flow is assumed to be laminar, isothermal and there is no mass transfer between phases. The initial condition of the imbibition processes was obtained from a drainage process for a strongly water-wet system. For this, a Bentheimer sandstone was completely filled with brine and supercritical CO2 was injected. The simulation was stopped when brine was drained by supercritical CO2 and the system reached the steady state conditions. This phase distribution was used as an initial boundary condition for the imbibition processes. The imbibition processes were performed in two opposite direction for different contact angles (100° and 110°). The effect of wettability and direction of brine on supercritical CO2 trapping were observed. The residual saturation of supercritical CO2 was significantly different in two opposite direction of brine flow. In the reverse imbibition process, normalized residual supercritical CO2 saturation values are increased but, the amount of normalized trapped supercritical CO2 values are decreased. It was mainly due to the amount of normalized free supercritical CO2 saturation values (which were equal to the difference between normalized residual supercritical CO2 saturation and normalized free supercritical CO2 saturation values).